Intestinal Parasitosis in Children and Adolescents of the Toromo Yukpa Ethnic Group, State of Zulia, Venezuela. Comparisons Between the Years 2002 And 2012 - Angela Bracho; Zulbey Rivero Rodríguez; Melary Rios; Ricardo Atencio; Rafael Villalobos; Luis Rodríguez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
The prevalence of intestinal parasites in indigenous children and adolescents from Toromo, State of Zu lia, was determined in 2012 and compared with the prevalence obtained in the same community in 2002. Both times, a stool sample was requested, which was subjected to a fresh coproparasitological examination with physiological saline and lugol, formalin-ether concentration and Kinyoun staining. The overall prevalence of intestinal parasites for the years 2002 and 2012 was 83.52% and 88.16%, respectively; protozoa prevailed over helminths. In both years, the species that occupied the first places were: Blastocystis spp. (51.65%/48.68%), Endolimax nana (37.36%/38.16%), Entamoeba coli, and helminths Ascaris lumbricoides (57.14%/63.16%), Trichuris trichiura (20.88%/23.68%) and Ancylostomideos (4.40%/23.68%). A statistically significant difference was observed in the prevalence of Iodamoeba butschlii, Strongyloides stercoralis and Ancylostomideos, when comparing the two dates. No intestinal coccidia were detected. Conclusions were that the maintenance and increase of intestinal parasites in individuals of the community is due to the lack of potable water, lack of environmental sanitation, poor education and cultural aspects of these indigenous people